Selective detection of Fe (III) via fluorescence turn-on mechanism with Rhodamine tethered poly(vinyl amine) microbeads - Demir, Zehra; Ozmen, Pinar; Karagoz, Bunyamin (Springer Science and Business Media LLC, 2021)
New reusable rhodamine tethered microbeads-based chemosensor was prepared and its fluorescent behaviors toward various transition-metal ions were investigated. Firstly, almost monodisperse (~ 2–5 µm in size) poly(vinyl formamide-co-ethylene glycol dimethacrylate) microbeads (Poly(VFA-co-EGDMA)) were prepared via precipitation polymerization. After hydrolysis of the microbeads in basic medium, terephthalaldehyde was tethered onto the microbeads via imine linkages. Subsequently, rhodamine hydrazide was linked to the resulting aldehyde functional microbeads in the same manner. The structural transformation of each step and the morphology of the microbeads were evaluated by FTIR and SEM, respectively. Rhodamine-decorated microbeads exhibited selective detection abilities on Fe (III) ions with high precision through the fluorescence turn-on mechanism. The limit of detection was found to be 1.5 µM. The job’s plot indicated a complexation ability as 1:1 stoichiometry between the chemosensor and Fe 3+ ion. The Benesi–Hildebrand plot revealed a binding constant (Ka) of 7 × 104 mol/L and the average fluorescence lifetime was measured as 48.9 ± 3.0 ns. From the material point of view, either the small particle size with a high surface area or crosslinked nature provided excellent sensing ability and stability of the microbeads in a heterogeneous medium. Besides, due to its densely crosslinked structure, rod beads can be easily reused after the ligand exchange process by simple filtration, which is a very important advantage for chemosensor recycling. These features offer a potential application as a chemosensor of Fe 3+ ion in aqueous solution.